Penggunaan Pill Card (Kartu Pengingat Minum Obat) untuk Kepatuhan Minum Obat pada Pasien Tuberkulosis - Alfi Syahar Yakub; Filadelvia Gaby.T; Nasrullah Nasrullah (Celebes Advance Health Journal, 2025)
Background: Tuberculosis (TB) is still one of the main health problems in Indonesia, One of the main challenges in handling it is the low level of patient adherence in undergoing long-term drug therapy. Low adherence can lead to treatment failure, relapse, and drug resistance. Objective: This study aims to evaluate the effectiveness of the use of pill cards (medication reminder cards) in improving TB patients' adherence to treatment. Methods: The methods used are a mixture of quantitative and qualitative. A total of 10 TB patients at the Minasa Upa Health Center became respondents. Quantitative data were obtained through MMAS-8 questionnaires before and after the intervention, while qualitative data were collected through in-depth interviews. Methods: The results showed that the average compliance score increased from 7.0 to 7.8 or by 11.43%. The results of the Wilcoxon test showed a significance value of p = 0.038 which showed that the use of pill cards has the potential to increase patient adherence in taking medications. Interviews show that pill cards help patients remember medication schedules and understand medication better. Results: Summarize the main findings of the article. Conclusions: Pill cards are a simple but effective medium in improving drug adherence for TB patients, and have the potential to be developed as a more comprehensive educational tool.